Potential of Cow Bone as a Basic Material for Hydroxyapatite-High Density Polyethylene Composites (HAp-HDPE) - Ramadani, Kurnia; Rismawati, Rismawati; Ismail, Ismail; Andriani, Titik (JURNAL KIMIA MULAWARMAN, 2024)
Cow bone has the potential to be used as a basic ingredient in the synthesis of hydroyapatite because it contains calcium. The addition of High Density Polyethylene (HDPE) to hydroyapatite aims to produce biocomposites that have better properties compared to the previous properties. The purpose of this study is to determine the characteristics of biocomposites with the HDPE:HAp in the ratio of 1: 2, 2: 1 and 3: 2 (%w / w). The method used is the sol-gel method and characterized by FTIR to see the bonding of functional groups and electron microscope to see the morphology of biocomposites. The biocomposites that have the best mechanical properties in this study are biocomposites with a ratio (HDPE: HAp) of 3: 2 with compressive and tensile strength values of 0.66 and 0.1290 N / mm2, density and water absorption values of 0.505 g / cm3 and 6,828% respectively and heat resistance with a temperature of 110 ° C experiencing a mass decrease of 0,675 g.